Analysis of NCTzen Student Reception on NCT Dream's Upload Towards Withdrawal of Sympathy from the Indonesian Society - Dholley Dwi Jatmiko Latabulo; Anjasmoro Dwi Pamungkas (Universitas Muhammadiyah Sidoarjo, 2022)
NCT Dream is one of the Korean Wave or Hallyu phenomena that is being loved by the Indonesian people. This study aims to find out how the process of meaning that NCTzen students have for uploading NCT Dream attracts sympathy from the Indonesian people (on the upload of Goyang Mendung Tanpo Udan on NCT Dream's Official Instagram) ). The researcher used audience reception analysis techniques and Stuart Hall's coding-decoding theory. Researchers used research methods in the form of qualitative. In this case, the data was obtained through in-depth interviews with NCTzen students, namely Martha, Aqwika, Aqwina, and Septy into three categories namely Hegemony-Dominant, Negotiation, and Opposition. The results showed that in this phenomenon; there were three informants in the Hegemony-Dominant category and one in the Negotiation category. This study found that the post can cause a sense of pride because of the adoption of local Indonesian culture, but this sympathy can be reduced by the negative stigmas that develop.